Calling out catcalling the rhetorical vision of Facebook users on catcalling in "catcalled in the Philippines" - Cruz, Rossane C. (College of Arts and Letters, University of the Philippines Diliman, 2019)
Because of the scarcity on the forms of street harassment, my study aimed to asked how catcalling is described as a sexual offense in the Philippines. To answer this, I looked into existing narratives on catcalling in a social media platform. There are a number of local online platforms where women narrate their experiences on sexual harassment. One of which is the Facebook page, Catcalled in the Philippines. Following a qualitative research design, I analyzed three selected posts and comments on catcalling on the Facebook page using Ernest Bormann's (1985) symbolic convergence theory to elicit the descriptions of the act in the Philippines. By employing the fantasy theme analysis as methodology, the artifacts revealed the fantasies of Facebook users concerning their attitudes and perceptions towards catcalling. There emerged recurring characters, settings, and plotlines from which women experience the act. These were classified into fantasy types, then crafted into rhetorical visions. From the analyses, the Facebook users involved in the selected posts and comment threads of the Facebook page view catcalling to be a sexual offense, seeing it as a war they need to fight. With the theory rooting from face-to-face group communication, I made use of McFarland and Ployhart's (2015) social media contextual framework to understand the distinct affordances of the social media platform. Facebook, in creating the rhetorical visions. This was also used to analyze how women share their narratives on the Facebook page. I argue that all of these stimuli hold an impact in the formation of the rhetorical visions and the disclosure of women in the social media platform. To supplement the analysis of the data, I conducted a face-to-face interview with one of the administrators of the Facebook page. In addition, I made use of the feminist standpoint theory as lens in comprehending the how the rhetorical visions were projected and how women narrate their catcalling experiences in the Facebook page. My analysis revealed that the Filipino women are being oppressed and marginalized through acts of sexual harassment, specifically acts of catcalling for my study. Also, there were certain stimuli that impacted the feminist standpoint.